2011
DOI: 10.1073/pnas.1100465108
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of natural allelic variation in Arabidopsis using a multiparent recombinant inbred line population

Abstract: To exploit the diversity in Arabidopsis thaliana, eight founder accessions were crossed to produce six recombinant inbred line (RIL) subpopulations, together called an Arabidopsis multiparent RIL (AMPRIL) population. Founders were crossed pairwise to produce four F1 hybrids. These F1s were crossed according to a diallel scheme. The resulting offspring was then selfed for three generations. The F4 generation was genotyped with SNP and microsatellite markers. Data for flowering time and leaf morphology traits we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
132
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(135 citation statements)
references
References 41 publications
2
132
0
1
Order By: Relevance
“…It has been suggested that power issues reduce the number of QTL observable with multiparent mapping lines (Keurentjes et al 2011). There were, for example, fewer QTL observed for flowering time using multiparent populations of A. thaliana (Kover et al 2009b;Huang et al 2011) than in studies that used mapping populations from intercrosses of two accessions. However, in this study the number of QTL identified (8 QTL for seed size and 9 QTL for seed number) is comparable to the other QTL studies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that power issues reduce the number of QTL observable with multiparent mapping lines (Keurentjes et al 2011). There were, for example, fewer QTL observed for flowering time using multiparent populations of A. thaliana (Kover et al 2009b;Huang et al 2011) than in studies that used mapping populations from intercrosses of two accessions. However, in this study the number of QTL identified (8 QTL for seed size and 9 QTL for seed number) is comparable to the other QTL studies.…”
Section: Discussionmentioning
confidence: 99%
“…polyallelism, genetic heterogeneity) by forward genetic approaches is difficult in spite of their suspected importance in human disease (McClellan and King 2010). Indeed, detecting multiallelism requires a multiple-parent QTL scheme, and this has only been recently implemented in a handful of model organisms (Huang et al 2011;Long et al 2014a). Furthermore, GWAS studies typically underestimate the contributions of mixed alleles (Thornton et al 2013).…”
Section: How When and Why Ligand Genes Are Likely Drivers Of Pattermentioning
confidence: 99%
“…Therefore, the THDC and FHC designs were examined. The THDC design is similar to the Arabidopsis multi-parental RIL design (Paulo et al, 2008;Huang et al, 2011), where the PIs are crossed in pairs to create two-way hybrids, which were then crossed in a diallel. Instead of a diallel cross, the FHC had a second generation of pairwise hybridisations.…”
Section: Comparison Of the Examined Mating Designsmentioning
confidence: 99%